Clinical and Radiographic Characteristics as Predictive Factors of Swelling and Trismus after Mandibular Third Molar Surgery: A Longitudinal Approach - José Manuel Pérez-González; Vicente Esparza-Villalpando; Ricardo Martínez-Rider; Miguel Ángel Noyola-Frías; Amaury Pozos-Guillén (Pain Research and Management)
Introduction. Factors that contribute to swelling and trismus are complex, and they are originated by surgical trauma. The aim of the present study was to determine whether clinical and radiographic factors could predict the level of swelling and trismus after lower third molar surgery, through longitudinal approach. Methodology. A prospective longitudinal trial was carried out. Forty-five patients of both genders with clinical and radiographic diagnosis of asymptomatic mandibular impacted third molar and with no intake of analgesic or anti-inflammatory drugs 12 h prior to surgery were recruited and evaluated in a 72 h follow-up period. A mixed repeated measures model and backward and restricted maximal likelihood methods were used to analyze the data. Results. Male gender, body mass index (BMI), the relation to the lingual and buccal walls, and age were determinants for predicting postoperative swelling and for exerting a significant influence (P<0.05). Conclusions. This study suggests the association of male gender, the relation to lingual and buccal walls, BMI, and age with measurement of swelling.